The imbalance between Treg and Th17 cells caused by FTY720 treatment in skin allograft rejection - Commodaro, Alessandra Goncalves [UNIFESP] (2012)
OBJECTIVES: FTY720 modulates CD4(+)T cells by the augmentation of regulatory T cell activity, secretion of suppressive cytokines and suppression of IL-17 secretion by Th17 cells. To further understand the process of graft rejection/acceptance, we evaluated skin allograft survival and associated events after FTY720 treatment.METHODS: F1 mice (C57BL/6xBALB/c) and C57BL/6 mice were used as donors for and recipients of skin transplantation, respectively. the recipients were transplanted and either not treated or treated with FTY720 by gavage for 21 days to evaluate the allograft survival. in another set of experiments, the immunological evaluation was performed five days post-transplantation. the spleens, axillary lymph nodes and skin allografts of the recipient mice were harvested for phenotyping (flow cytometry), gene expression (real-time PCR) and cytokine (Bio-Plex) analysis.RESULTS: the FTY720 treatment significantly increased skin allograft survival, reduced the number of cells in the lymph nodes and decreased the percentage of Tregs at this site in the C57BL/6 recipients. Moreover, the treatment reduced the number of graft-infiltrating cells and the percentage of CD4(+) graft-infiltrating cells. the cytokine analysis (splenocytes) showed decreased levels of IL-10, IL-6 and IL-17 in the FTY720-treated mice. We also observed a decrease in the IL-10, IL-6 and IL-23 mRNA levels, as well as an increase in the IL-27 mRNA levels, in the splenocytes of the treated group. the FTY720-treated mice exhibited increased mRNA levels of IL-10, IL-27 and IL-23 in the skin graft.CONCLUSIONS: Our results demonstrated prolonged but not indefinite skin allograft survival by FTY720 treatment. This finding indicates that the drug did not prevent the imbalance between Tr1 and Th17 cells in the graft that led to rejection.